EFFECT OF SOYBEAN PLANT POPULATIONS ON YIELD AND PRODUCTIVITY OF CASSAVA AND SOYBEAN GROWN IN A CASSAVA-BASED INTERCROPPING SYSTEM - Emmanuel Ukaobasi Mbah; E. Ogidi (Tropical and Subtropical Agroecosystems, 2012)
Intercropping cassava (Manihot esculenta Crantz), with varying soybean [Glycine max (L.) Merrill] plant populations may influence not only the performance of the component crops but also the residual nitrogen contribution to the cropping system. The treatment scheme was cassava fixed at 100% of its sole crop population of 10,000 plants ha-1 while soybean was varied at 25, 50, 75 and 100% of its sole crop population of 266,000 plants ha-1, representing 66,500; 133,000; 199,500 and 266,000 plants ha-1, respectively. The experiment was laid out in a randomized complete block design with three replicates. Fresh tuber yield in cassava increased as soybean population increased to the highest amount used in the study while number of pods plant-1 and seed weight plant-1 in soybean were depressed by intercropping in the two cropping seasons. However, soybean grain yield was significantly increased with increase in population due to higher aggregate plant populations per unit area in the intercrop. Averaged over the two cropping seasons, productivity showed that cassava/soybean intercrop, especially at the highest soybean population gave the highest yield advantage in terms of total land equivalent ratio, (2.00), land equivalent coefficient (2.41), crop yield equivalent for cassava (31.07 t ha-1) and for soybean (2.25 t ha-1), monetary equivalent ratio (1.56), total gross monetary returns (N170,311.52) and total net profit (N74,488.02). This implies that for maximum financial returns, additive intercropping of cassava and soybean at 100% cassava + 100% soybean is recommended because of improved productivity of the system as well as bonus yield and improved health of the farmers from the associated soybean component are achieved.